La reformulation du récit : relations texte ‒ discours ‒ langue dans l’optique didactique - Karpińska-Szaj, Katarzyna; Lewandowska, Agata; Wojciechowska, Bernadeta (Studia Romanica Posnaniensia, 2019)
The interweaving of textual, discoursal and linguistic narrative data depends on the pedagogical aims and characteristics of the learner, for whom working with a text is an opportunity to develop linguistic communicative competences and learning competence. The aim of the article is to assess the pedagogical value of the experimental procedure focused on the task of reformulation of narrative texts (stories) offered in two pedagogical contexts at beginners’ level. The analysis addresses text characteristics (the narrative scheme) and the language structures used in the performance of the reformulation task, which, in its particular context, has the value of strategic learning/teaching.